Isolation, identification and their biological characteristics of pathogens of potato Fusarium wilt in Yinshan area, Inner Mongolia - JIA Ruifang; KANG Liru; ZHAO Yuanzheng; AN Le; ZHANG Zhiwei; ZHAO Jun; XU Limin; ZHANG Jian (浙江大学学报. 农业与生命科学版)
To clarify the pathogen species and their biological characteristics of potato Fusarium wilt in Yinshan area of Inner Mongolia, 463 samples infected with potato wilt were selected as objects from 2018 to 2019. Pathogens were isolated and purified by tissue isolation and the pathogenicity was detected by Koch’s postulate. The types and classification of pathogens were identified by morphology and elongation factor 1α (EF1α) sequencing analysis, and the comparative study of their biological characteristics was conducted. The results showed that 139 strains of Fusarium spp. caused potato Fusarium wilt, which belonging to 10 species, among them, 64 strains of F. oxysporum, 30 strains of F. equiseti, 10 strains of F. verticillioides, 12 strains of F. acuminatum, four strains of F. redolens, six strains of F. solani, seven strains of F. tricinctum, two strains of F. proliferum, three strains of F. sambucinum and one strain of F. chlamydosporum were identified, and the isolation rate of F. oxysporum was 46.0% and it was the dominant isolate. The results of biological characteristic determination showed that the optimum growth pH value of all tested strains on potato dextrose agar (PDA) was 7-9. The optimum growth temperatures of F. acuminatum and F. sambucinum were both 25 ℃, and the other Fusarium species were 30 ℃. Further analysis of pathogenicity showed that there were differences among ten Fusarium wilt pathogens. The disease index caused by F. oxysporum was 60.19, and it was higher than other nine Fusarium species, which was the dominant pathogen of potato Fusarium wilt in Yinshan area of Inner Mongolia.